Examination for Susceptibility of CAE - Kusza, Szilvia; Bősze, Zsuzsanna; Kukovics, Sándor; Jávor, András (Acta Agraria Debreceniensis, 2004)
Caprine Arthritis Encephalitis (CAE) is a group of diseases in goats caused by a retrovirus, namely the Caprine Arthritis Encephalitis Virus. CAEV belongs to the lentivirus group within the retrovirus family. The CAEV is intimately associated with white blood cells, therfore any body secretions which contain white blood cells are a potential source of virus to other goats in the flock. Once goats are infected with CAEV, it remains infected for life and has to be eliminated. Since not all goats infected with CAEV progress to disease, very important to test goats for infection using a serology test (ELISA, AGID, IDT). These serological tests demonstrate the presence of antibodies to CAEV in goat serum or detect the virus genome in the white blood cells. However, Swiss results (Dolf and Ruff, 1994) pointed out individual and species differencies in predisposition for this disease. This result was considered as a starting point to our examination. Microsatellite analysis was used in order to find whether there was any association between genotype and serological results, and to look for a marker associated with this disease. To date, altogether 135 goats have been examined. Unfortunately, a significant association between serological results and genotype was not found using the Chi2 test